Entry Inhibitors in HIV Therapy - Reeves, Jacqueline D.; Derdeyn, Cynthia A. (Milestones in Drug Therapy, 2007)
Entry Inhibitors in HIV Therapy presents the current status of this relatively new and highly dynamic class of inhibitors and provides a unique overview of obstacles and considerations for HIV entry inhibition compared to other antiretroviral targets. The introductory chapters of this book present an overview of entry inhibitors, review current knowledge of how Env mediates entry, and discuss the challenge of genetic diversity in this region of the viral genome. Subsequent chapters feature current information on individual classes of entry inhibitors that target each step of the virus entry pathway, from attachment to membrane fusion. There is an emphasis on the complex determinants of entry inhibitor susceptibility, resistance mechanisms, the need for clinical phenotyping, and how these issues create new challenges for antiretroviral therapy. Encouraging pre-clinical studies of entry inhibitors as microbicidesare also discussed. The final chapters highlight the current status of entry inhibitors in clinical studies, the major milestone achieved with FDA approval of enfuvirtide, and review drug development, past and present. In summary, this book presents a comprehensive and current overview of entry inhibitors from an expert panel of authors with diverse backgrounds and perspectives, incorporating many unrelenting successes against a backdrop of formidable challenges. It is of interest to basic science researchers as well as clinical physicians.